Method for recovering phosphorus in sludge pyrolysis residues, flocculant synthesis method and application
By acid extraction and adsorption resin purification of sludge pyrolytic residues, high-purity struvite is extracted, and the remaining residues are converted into flocculant, the land resource waste and environmental pollution problems of landfill treatment of sludge pyrolytic residues are solved, and efficient resource utilization and sustainable environmental protection are achieved.
Patent Information
- Application Number
- CN202411764619.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-04
AI Technical Summary
The landfill treatment of sludge pyrolytic residues poses a risk of waste of land resources, high costs, and harmful substances contaminate soil and groundwater, making it difficult to achieve resource utilization.
By purifying the pyrolyzed residue of the sludge, purifying the adsorption resin and crystallization reaction, phosphorus elements are extracted and purified to form high-purity struvite, and the remaining sludge residue is converted into a flocculant, achieving secondary utilization of resources.
The phosphorus resources in the pyrolysis residue of sludge have been recovered, the landfill volume and environmental pollution risks have been reduced, high-quality agricultural fertilizers have been provided, and the resource utilization rate of the sludge treatment process has been improved, which is in line with the concept of sustainable development and circular economy.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the field of sludge treatment, and more specifically, to a method for recovering phosphorus from sludge pyrolysis residue, a method for synthesizing a flocculant, and an application thereof. Background Art
[0002] With the acceleration of my country's urbanization process, the amount of water treated by urban sewage treatment plants continues to rise, and it still shows a rapid growth trend every year. In the process of municipal sewage treatment, the output of sludge as a by-product is also increasing.
[0003] As ecological and environmental protection is increasingly valued, the stabilization, reduction, harmlessness and resource disposal of sludge have become key issues that need to be addressed. At present, my country mainly uses incineration and pyrolysis technologies to treat sludge. Although incineration technology can treat sludge, it has many disadvantages, such as the easy production of a large amount of dioxins and other harmful gases, causing secondary pollution to the environment, and high energy consumption during the treatment process.
[0004] Pyrolysis technology is the treatment of sludge under oxygen-poor and high-temperature conditions. This technology has significant advantages. It can effectively reduce the amount of sludge by about 90%, producing only about 10% of sludge residue. At the same time, it can greatly curb the generation of dioxins, thereby greatly reducing the risk of secondary pollution to the environment. However, the traditional treatment method for the residues produced by sludge pyrolysis is mainly landfill. This landfill disposal method has obvious shortcomings. It not only requires the occupation of a large area of land resources, resulting in a waste of land resources, but also incurs high costs during transportation. What is more serious is that the landfilled sludge residues may cause soil pollution, and the harmful substances in them may penetrate into the soil, thereby affecting the quality and ecological functions of the soil, and causing serious harm to the entire ecological environment. Summary of the invention
[0005] In order to recycle phosphorus resources from sludge pyrolysis residues and perform secondary utilization of the residues, the present application provides a method for recovering phosphorus from sludge pyrolysis residues, a method for synthesizing a flocculant and applications thereof.
[0006] The present application provides a method for recovering phosphorus from sludge pyrolysis residues using the following technical solution: A method for recovering phosphorus from sludge pyrolysis residues comprises the following steps: 90-110 parts by weight of the sludge pyrolysis residue are dried at 105-110° C. for 1.5-2.5 hours, and then ground and sieved after drying; the sieved sludge pyrolysis residue is placed in a 0.1-0.8 mol / L hydrochloric acid solution at a liquid-solid ratio of 10-50 mL / g, reacted for 2-6 hours, and after the reaction, solid-liquid separation is performed to obtain a phosphorus-containing extract and residual sludge residue; Treating the phosphorus-containing extract with an adsorption resin for 2-3 hours to obtain a phosphorus-purified solution; The pH of the phosphorus purification solution is adjusted to 9-11, and a crystallization reaction is carried out under the condition that the molar ratio of magnesium, nitrogen and phosphorus is (0.8-1.2):(1-1.6):1 to obtain struvite.
[0007] By adopting the above technical scheme, by subjecting the sludge pyrolysis residue to acid leaching treatment under the conditions of this application, the phosphorus element in the sludge residue can be dissolved in a large amount into the extract, and the phosphorus leaching efficiency is high, which lays a good foundation for the subsequent recovery of phosphorus. The phosphorus-containing extract is treated with an adsorption resin for 2-3 hours to obtain a phosphorus purified solution. The adsorption resin can selectively remove impurity cations (such as metal ions such as aluminum and iron) in the acid solution. If these impurity ions are not removed, the purity and quality of the subsequent struvite crystallization will be affected. The purified phosphorus purified solution is crystallized under specific pH and molar ratio conditions to obtain struvite, ensuring that phosphorus elements and elements such as magnesium and nitrogen are crystallized in the best proportion to form struvite, thereby obtaining a high-purity struvite product. High-purity struvite can be used as a high-quality agricultural fertilizer, and the phosphorus element it contains can be more effectively absorbed and utilized by crops, thereby improving the efficiency of agricultural production. In actual production, the purity of the struvite product obtained can reach more than 90%, wherein the effective content of phosphorus is high, which meets the requirements of agricultural fertilizers for phosphorus content.
[0008] The traditional landfill treatment of sludge pyrolysis residue has many environmental problems. Since the sludge residue contains harmful substances (such as heavy metals), these harmful substances may enter the soil and groundwater with rainwater infiltration during the landfill process, causing soil and groundwater pollution and destroying the balance of the ecological environment. However, this solution recovers phosphorus from the sludge residue and makes most of the sludge residue a resource, greatly reducing the amount of residue that needs to be landfilled, thereby reducing the risk of landfilling causing soil and groundwater pollution, which is of great significance to the protection of soil and groundwater resources.
[0009] Optionally, the adsorption resin includes one of polyacrylamide resin, weakly acidic cation exchange resin, and styrene-divinylbenzene resin containing phosphonic acid groups.
[0010] By adopting the above technical solution, the polyacrylamide resin has a polymer chain structure, which can produce flocculation effect on impurity ions through the extension and entanglement of molecular chains in the solution. When treating phosphoric acid solution, it can not only flocculate some suspended solid impurity particles to prevent them from interfering with the subsequent phosphorus recovery process, but also its amide group and other functional groups can interact with some metal cations (such as iron, aluminum, etc.) in the solution through hydrogen bonds, electrostatic attraction, etc. for adsorption, and the concentration of metal cations can be reduced to a certain extent, so that the quality of phosphorus purification solution is significantly improved.
[0011] Weakly acidic cation exchange resins carry weakly acidic exchange groups such as carboxylic acid groups. In phosphoric acid solutions, due to their strong affinity for hydrogen ions, they can preferentially adsorb metal cations in the solution under acidic conditions, while adsorbing less phosphorus, thereby effectively separating phosphorus from metal impurities and improving the purity of the phosphorus purification solution. When the weakly acidic cation exchange resin is saturated with adsorption, it can be regenerated using regenerants such as dilute hydrochloric acid or dilute sulfuric acid. The regeneration process is relatively simple, and the amount of regenerant used is relatively small, close to the theoretical chemical equivalent. Through regeneration treatment, the resin can restore its ion exchange capacity and can be reused many times. This not only reduces the long-term use cost of the adsorption resin, but also reduces the generation of waste, which is in line with the concept of sustainable development.
[0012] Styrene-divinylbenzene resin containing phosphonic acid groups has a strong affinity and selectivity for metal cations. In phosphoric acid solutions, phosphonic acid groups can form stable complexes with a variety of metal cations, especially heavy metal ions, to achieve efficient adsorption. Compared with some common adsorption resins, it can adsorb more impurity cations, greatly improving the purity of phosphorus purification liquid. The styrene-divinylbenzene resin skeleton gives the resin good mechanical strength and chemical stability, enabling it to stably exist in acidic solutions with higher concentrations and exert an adsorption effect.
[0013] Optionally, the preparation method of the styrene-divinylbenzene resin containing phosphonic acid groups is: The styrene-divinylbenzene resin is washed with deionized water until the conductivity of the deionized water is less than 50 μS / cm, and then dried after washing; the styrene-divinylbenzene resin and anhydrous zinc chloride are mixed in a mass ratio of 10:(0.2-0.3), and toluene is added for stirring, and chloromethyl ether is added to the toluene, and the mass ratio of chloromethyl ether to styrene-divinylbenzene resin is (2-4):10, and the reaction temperature is controlled at 0-5° C. After the addition of chloromethyl ether is completed, the temperature is raised to 30-35° C., and the reaction is carried out for 4-6 hours. After the reaction is completed, the reaction product is washed until the pH value is neutral and dried; The above reaction product is mixed with phosphorous acid in a mass ratio of (1-1.5):1, and added to N,N-dimethylformamide. The reaction product needs to be immersed in N,N-dimethylformamide, and the temperature is raised to 100-120°C, and the reaction is carried out for 6-8 hours; After the reaction is completed, the reaction product is washed to neutrality and then dried to obtain a styrene-divinylbenzene resin containing a phosphonic acid group.
[0014] By adopting the above technical solution, the styrene-divinylbenzene resin is washed with deionized water until the conductivity is less than 50μS / cm, which can effectively remove the residual electrolytes, water-soluble impurities and possible small molecular organic matter on the surface and internal pores of the resin. These impurities will interfere with subsequent chemical reactions and affect the performance and purity of the resin. The chloromethylated product is reacted with phosphorous acid in N,N-dimethylformamide, and phosphorous acid and chloromethyl undergo a substitution reaction, successfully introducing a phosphonic acid functional group on the resin skeleton. The introduction of the phosphonic acid group gives the resin a high affinity and selectivity for metal cations, and can form stable complexes with a variety of metal ions, thereby achieving efficient adsorption of metal cations. The preparation method of the present application greatly improves the ability of the resin to remove metal impurities when purifying phosphorus in a phosphoric acid solution, which is conducive to obtaining a high-purity phosphorus purification solution.
[0015] Optionally, the phosphonic acid group-containing styrene-divinylbenzene resin is further treated as follows: The styrene-divinylbenzene resin containing phosphonic acid groups is soaked in a hydrochloric acid solution with a mass concentration of 2-5%, and the resin is washed to neutral after soaking for 4-6 hours. The resin is then soaked in a sodium hydroxide solution with a mass concentration of 2-5%, and the resin is washed to neutral after soaking for 4-6 hours. The resin after acid-base treatment is soaked in a 0.5-1 mol / L sulfuric acid solution for 2-4 hours.
[0016] By adopting the above technical scheme, after soaking in acid and alkali solutions, on the one hand, the resin surface can be effectively cleaned to reduce the interference of impurities on the subsequent ion exchange and adsorption process, and on the other hand, the functional groups of the resin can be further activated. The resin after acid and alkali treatment is soaked in a 0.5-1mol / L sulfuric acid solution for 2-4 hours, the main purpose of which is to transform the resin into a specific ionic form. The sulfate ions exchange with the hydrogen ions on the resin, so that the resin has more active groups in the form of hydrogen sulfate ions. This transformed resin can better adapt to the acidic environment of the solution when treating phosphoric acid solutions, and form more stable complexes or ion pairs with metal cations during ion exchange and adsorption, further improving the adsorption capacity and selectivity for metal cations.
[0017] In a second aspect, the present application provides a flocculant and a method for synthesizing the same, using the following technical solution: A flocculant, which is prepared by the excess sludge residue as claimed in claim 1.
[0018] A method for synthesizing a flocculant comprises the following steps: Mix a hydrochloric acid solution with a mass concentration of 10%-30% with the remaining sludge residue at a liquid-solid ratio of 4-7 mL / g, heat to 80-140°C, reflux and stir for 2-5 hours, and after the reaction is completed, a primary aluminum ferric chloride solution can be obtained; The aluminum ferric chloride primary liquid is mixed with sodium aluminate in a mass ratio of (0.8-2.4):1, and a polymerization reaction is carried out at 60-100°C to obtain a polyaluminum ferric chloride solution flocculant after the reaction is completed.
[0019] By adopting the above technical scheme, the residual sludge residue after phosphorus extraction is used as raw material to synthesize flocculants, realizing the secondary development and utilization of resources. After the phosphorus recovery process, the main components such as aluminum and iron in the sludge residue still retain a certain content. Through acid leaching and polymerization reaction steps, the sludge residue that may have been discarded is converted into a valuable flocculant product, which improves the resource utilization rate of the entire sludge treatment process, reduces the discharge of waste, and conforms to the concept of sustainable development and circular economy. By controlling the concentration of hydrochloric acid solution, liquid-solid ratio and heating reflux stirring conditions to synthesize aluminum ferric chloride primary solution, the aluminum, iron and other metal elements in the sludge residue can be fully dissolved and reacted to form aluminum ferric chloride compounds with high activity. Subsequently, it is polymerized with sodium aluminate to obtain a polyaluminum ferric chloride solution flocculant with good flocculation performance. It can be rapidly hydrolyzed in water to form a polynuclear hydroxyl complex, and through a variety of action mechanisms such as adsorption and electrical neutralization, adsorption bridging and net capture and sweeping, it can quickly remove suspended particles, colloidal substances and some soluble organic matter and phosphate pollutants in water. The flocculant synthesis method achieves the dual goal of "treating waste with waste".
[0020] Optionally, nano calcium carbonate is added when the aluminum ferric chloride primary liquid is mixed with sodium silicate, the particle size of the nano calcium carbonate is 30-80 nm, and the amount of the nano calcium carbonate added is 1.5-3.5% of the mass of the primary liquid.
[0021] By adopting the above technical scheme, nano calcium carbonate can enhance the adsorption bridging effect, improve the electrical neutralization ability, improve the stability of the flocculant, prevent excessive hydrolysis, increase applicability, buffer pH changes, and synergistically precipitate heavy metal ions due to its small particle size and large specific surface area in the aluminum chloride ferric flocculation system, thereby improving the flocculation efficiency, heavy metal removal rate and adaptability to complex water quality.
[0022] In a third aspect, the present application provides an application of a flocculant, using the following technical solution: The invention discloses an application of a flocculant, wherein the flocculant is applied to municipal sewage.
[0023] Preferably, the dosage of the flocculant in municipal sewage is 0.025-0.1 mL / L.
[0024] By adopting the above technical solution, the flocculant can react with soluble phosphate in municipal sewage at a dosage of 0.025-0.1mL / L. Phosphorus is removed from sewage by forming precipitation or complex with phosphorus ions, and the removal rate of total phosphorus can reach 60%-90%, which effectively reduces the phosphorus content in municipal sewage and alleviates the risk of eutrophication of water bodies, which is of great significance for protecting the ecological environment of receiving water bodies.
[0025] In summary, this application has the following beneficial effects: 1. The phosphorus recovery method from sludge pyrolysis residue of the present application efficiently extracts and purifies phosphorus into high-purity struvite products through acid leaching, adsorption resin purification and crystallization reaction. It not only realizes the resource utilization of sludge residue, reduces the landfill volume and the environmental risks it brings, but also provides high-quality agricultural fertilizer, which is of great significance to protecting soil and groundwater resources and improving agricultural production efficiency.
[0026] 2. The flocculant synthesis method of the present application uses the remaining sludge residue after phosphorus extraction as raw material, and converts it into a valuable flocculant product through acid leaching and polymerization reaction. It not only improves the resource utilization rate of the sludge treatment process and reduces waste discharge, but also the synthesized polyaluminum ferric chloride solution flocculant has excellent performance and can effectively remove a variety of pollutants in water, achieving the dual goals of secondary development and utilization of resources and "waste treatment with waste", which is in line with the concept of sustainable development and circular economy.
[0027] 3. The application of the flocculant of the present application, by adding 0.025-0.1 mL / L, can effectively react with soluble phosphates, significantly reduce the phosphorus content, alleviate the risk of eutrophication of water bodies, and is of great significance to the protection of the ecological environment. DETAILED DESCRIPTION
[0028] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0029] Preparation Example of Styrene-Divinylbenzene Resin Containing Phosphonic Acid Group Preparation Example 1 Preparation of a phosphonic acid group-containing styrene-divinylbenzene resin: 10 kg of styrene and 2 kg of divinylbenzene were added to a polymerization reactor, and then 5 kg of toluene was added. The stirrer was turned on and the stirring speed was adjusted to 300 rpm. Nitrogen was introduced into the reactor for replacement to remove the air in the reactor. Under the protection of nitrogen, the temperature in the reactor was raised to 80° C.; Then, the initiator benzoyl peroxide was added into the reactor to initiate the polymerization reaction. The temperature was kept at 70-80°C during the reaction and the reaction time was 5 hours. After the polymerization reaction is completed, heating and stirring are stopped, the reaction product is cooled to room temperature, the polymerization product is separated by filtration to obtain styrene-divinylbenzene resin, and the styrene-divinylbenzene resin is repeatedly washed with a large amount of deionized water until the conductivity of the washing water is lower than 50 μS / cm, and the washed styrene-divinylbenzene resin is dried in a vacuum oven at 60° C.; 10 kg of styrene-divinylbenzene resin was added to the reactor, 250 g of anhydrous zinc chloride was added as a catalyst, and 5 kg of toluene was added again, and the materials in the reactor were evenly dispersed by stirring; 3 kg of chloromethyl ether was added dropwise to the reactor. The reaction temperature was controlled at 3 °C during the addition. After the addition of chloromethyl ether was completed, the temperature in the reactor was raised to 32 °C and the reaction was continued for 5 hours. After the reaction, the reaction product is cooled to room temperature, washed with a large amount of ethanol, and the washed product is repeatedly washed with deionized water until the pH value of the washing water is close to neutral, and the reaction product is dried in a vacuum oven at 60°C; the dried reaction product is mixed with 8kg of phosphorous acid and 10kg of N,N-dimethylformamide in a reaction container, the stirrer is turned on, the temperature in the reaction container is raised to 110°C, and the reaction is carried out for 7 hours. After the reaction is completed, the reaction product is cooled to room temperature, and the solid product is separated to obtain a styrene-divinylbenzene resin containing a phosphonic acid group, which is then washed with a large amount of deionized water. The washed resin is soaked in a 0.3 mol / L dilute sodium hydroxide solution, and then washed with deionized water until neutral, and the washed styrene-divinylbenzene resin containing a phosphonic acid group is dried in a vacuum oven at 50°C.
[0030] Preparation Example 2 Preparation of a styrene-divinylbenzene resin containing phosphonic acid groups: The difference from Preparation Example 1 is that 2 kg of chloromethyl ether is added dropwise into the reaction kettle.
[0031] Preparation Example 3 Preparation of a styrene-divinylbenzene resin containing phosphonic acid groups: The difference from Preparation Example 1 is that 4 kg of chloromethyl ether is added dropwise into the reaction kettle.
[0032] Preparation Example 4 Preparation of a styrene-divinylbenzene resin containing phosphonic acid groups: The difference from Preparation Example 1 is that the reaction product is mixed with 6.6 kg of phosphorous acid and 10 kg of N,N-dimethylformamide in a reaction container.
[0033] Preparation Example 5 Preparation of a styrene-divinylbenzene resin containing phosphonic acid groups: The difference from Preparation Example 1 is that the reaction product is mixed with 10 kg of phosphorous acid and 10 kg of N,N-dimethylformamide in a reaction container.
[0034] Preparation Example 6 Preparation of a styrene-divinylbenzene resin containing phosphonic acid groups: The difference from Preparation Example 1 is that the styrene-divinylbenzene resin containing phosphonic acid groups is immersed in a hydrochloric acid solution with a mass concentration of 3%, and the resin is washed to neutral after immersion for 5 hours, and then the resin is immersed in a sodium hydroxide solution with a mass concentration of 3%, and washed to neutral after immersion for 5 hours, and the resin after acid-base treatment is immersed in a 0.8 mol / L sulfuric acid solution for 3 hours.
[0035] Preparation Example 7 Preparation of a styrene-divinylbenzene resin containing phosphonic acid groups: The difference from Preparation Example 6 is that the resin after acid-base treatment is immersed in a 0.5 mol / L sulfuric acid solution for 3 hours.
[0036] Preparation Example 8 Preparation of a styrene-divinylbenzene resin containing phosphonic acid groups: The difference from Preparation Example 6 is that the resin after acid-base treatment is immersed in 1 mol / L sulfuric acid solution for 3 hours.
[0037] Preparation Example 9 A preparation of styrene-divinylbenzene resin: 10 kg of styrene and 2 kg of divinylbenzene were added to a polymerization reactor, and then 5 kg of toluene was added. The stirrer was turned on and the stirring speed was adjusted to 300 rpm. Nitrogen was introduced into the reactor for replacement to remove the air in the reactor. Under the protection of nitrogen, the temperature in the reactor was raised to 80° C.; Then, the initiator benzoyl peroxide was added into the reactor to initiate the polymerization reaction. The temperature was kept at 70-80°C during the reaction and the reaction time was 5 hours. After the polymerization reaction is completed, heating and stirring are stopped, the reaction product is cooled to room temperature, and the polymerization product is separated by filtration to obtain styrene-divinylbenzene resin, which is repeatedly washed with a large amount of deionized water until the conductivity of the washing water is lower than 50 μS / cm. The washed styrene-divinylbenzene resin is dried in a vacuum oven at 60°C.
[0038] Preparation Example 10 Preparation of a phosphonic acid group-containing styrene-divinylbenzene resin: The difference from Preparation Example 6 is that no acid-base treatment is performed, and the prepared phosphonic acid group-containing styrene-divinylbenzene resin is immersed in a 0.8 mol / L sulfuric acid solution for 3 hours. Example
[0039] Example 1 A method for recovering phosphorus from sludge pyrolysis residue and preparation of flocculant: Dry 100 kg of sludge pyrolysis residue at 108±2°C for 2 h, grind the sludge pyrolysis residue in a ball mill, and pass through an 80-mesh sieve after grinding; The sludge residue was placed in a 0.5 mol / L hydrochloric acid solution at a liquid-solid ratio of 30 mL / g, and reacted for 4 hours. After the reaction, solid-liquid separation was performed by filtration to obtain a phosphorus-containing extract and residual sludge residue; The phosphorus-containing extract is treated with an adsorption resin for 3 hours, wherein the adsorption resin is polyacrylamide resin, to obtain a phosphorus-purified solution; The phosphorus purification liquid is adjusted to pH=10 by sodium hydroxide solution, magnesium chloride hexahydrate crystals and ammonium chloride solid are added to the phosphorus essence liquid, and a crystallization reaction is carried out under the condition of adjusting the molar ratio of Mg:N:P=1:1.3:1 to obtain struvite.
[0040] A hydrochloric acid solution with a mass concentration of 20% is mixed with the remaining sludge residue at a liquid-solid ratio of 5 mL / g, and the mixed solution is heated to 110° C. and refluxed and stirred for 4 hours. After the reaction is completed, a primary aluminum ferric chloride solution can be obtained; The aluminum ferric chloride primary liquid and solid sodium aluminate are mixed in a reaction container at a mass ratio of 1.5:1, and a polymerization reaction is carried out at 80° C. After the reaction is completed, a polyaluminum ferric chloride solution flocculant is obtained.
[0041] Example 2 A method for recovering phosphorus from sludge pyrolysis residue and preparing flocculant: The difference from Example 1 is that the sludge residue is placed in a 0.5 mol / L hydrochloric acid solution at a liquid-solid ratio of 10 mL / g and reacted for 4 hours.
[0042] Example 3 A method for recovering phosphorus from sludge pyrolysis residue and preparing flocculant: The difference from Example 1 is that the sludge residue is placed in a 0.5 mol / L hydrochloric acid solution at a liquid-solid ratio of 50 mL / g and reacted for 4 hours.
[0043] Example 4 A method for recovering phosphorus from sludge pyrolysis residue and preparing flocculant: The difference from Example 1 is that the phosphorus purification liquid is adjusted to pH=9.
[0044] Example 5 A method for recovering phosphorus from sludge pyrolysis residue and preparing flocculant: The difference from Example 1 is that the phosphorus purification liquid is adjusted to pH=11.
[0045] Example 6 A method for recovering phosphorus from sludge pyrolysis residue and preparing flocculant: The difference from Example 1 is that the molar ratio of phosphorus purification liquid to magnesium and nitrogen is Mg:N:P=0.8:1.6:1.
[0046] Example 7 A method for recovering phosphorus from sludge pyrolysis residue and preparing flocculant: The difference from Example 1 is that the molar ratio of phosphorus purification liquid to magnesium and nitrogen is Mg:N:P=1.2:1:1.
[0047] Example 8 A method for recovering phosphorus from sludge pyrolysis residue and preparing flocculant: The difference from Example 1 is that the adsorption resin is D113 weakly acidic cation exchange resin.
[0048] Example 9 A method for recovering phosphorus from sludge pyrolysis residue and preparing a flocculant: The difference from Example 1 is that the adsorption resin is a styrene-divinylbenzene resin containing a phosphonic acid group, and the styrene-divinylbenzene resin containing a phosphonic acid group is prepared by Preparation Example 1.
[0049] Example 10 A method for recovering phosphorus from sludge pyrolysis residue and preparing flocculant: The difference from Example 9 is that the styrene-divinylbenzene resin containing phosphonic acid groups is prepared by Preparation Example 2.
[0050] Embodiment 11 A method for recovering phosphorus from sludge pyrolysis residue and preparing flocculant: The difference from Example 9 is that the styrene-divinylbenzene resin containing phosphonic acid groups is prepared by Preparation Example 3.
[0051] Example 12 A method for recovering phosphorus from sludge pyrolysis residue and preparing flocculant: The difference from Example 9 is that the styrene-divinylbenzene resin containing phosphonic acid groups is prepared by Preparation Example 4.
[0052] Example 13 A method for recovering phosphorus from sludge pyrolysis residue and preparing flocculant: The difference from Example 9 is that the styrene-divinylbenzene resin containing phosphonic acid groups is prepared by Preparation Example 5.
[0053] Embodiment 14 A method for recovering phosphorus from sludge pyrolysis residue and preparing a flocculant: The difference from Example 9 is that the styrene-divinylbenzene resin containing phosphonic acid groups is prepared by Preparation Example 6.
[0054] Embodiment 15 A method for recovering phosphorus from sludge pyrolysis residue and preparing flocculant: The difference from Example 9 is that the styrene-divinylbenzene resin containing phosphonic acid groups is prepared by Preparation Example 7.
[0055] Example 16 A method for recovering phosphorus from sludge pyrolysis residue and preparing flocculant: The difference from Example 9 is that the styrene-divinylbenzene resin containing phosphonic acid groups is prepared by Preparation Example 8.
[0056] Embodiment 17 A method for recovering phosphorus from sludge pyrolysis residue and preparing flocculant: The difference from Example 1 is that a hydrochloric acid solution with a mass concentration of 20% is mixed with the remaining sludge residue at a liquid-to-solid ratio of 4 mL / g.
[0057] Embodiment 18 A method for recovering phosphorus from sludge pyrolysis residue and preparing flocculant: The difference from Example 1 is that a hydrochloric acid solution with a mass concentration of 20% is mixed with the remaining sludge residue at a liquid-to-solid ratio of 7 mL / g.
[0058] Embodiment 19 A method for recovering phosphorus from sludge pyrolysis residue and preparing flocculant: The difference from Example 1 is that the aluminum ferric chloride primary liquid and solid sodium aluminate are mixed in a reaction container at a mass ratio of 0.8:1.
[0059] Embodiment 20 A method for recovering phosphorus from sludge pyrolysis residue and preparing flocculant: The difference from Example 1 is that the aluminum ferric chloride primary liquid and solid sodium aluminate are mixed in a reaction container at a mass ratio of 2.4:1.
[0060] Embodiment 21 A method for recovering phosphorus from sludge pyrolysis residue and preparing flocculant: The difference from Example 1 is that nano calcium carbonate is added when the aluminum ferric chloride primary liquid is mixed with solid sodium aluminate. The particle size distribution of the nano calcium carbonate is 30-80nm, and the amount of the nano calcium carbonate added is 2.5% of the mass of the primary liquid.
[0061] Comparative Example Comparative Example 1 A method for recovering phosphorus from sludge pyrolysis residue and preparing flocculant: The difference from Example 1 is that the molar ratio of phosphorus purification liquid to magnesium and nitrogen is Mg:N:P=0.7:1.7:1.
[0062] Comparative Example 2 A method for recovering phosphorus from sludge pyrolysis residue and preparing flocculant: The difference from Example 9 is that the styrene-divinylbenzene resin is prepared by Preparation Example 9.
[0063] Comparative Example 3 A method for recovering phosphorus from sludge pyrolysis residue and preparing a flocculant: The difference from Example 14 is that the styrene-divinylbenzene resin containing phosphonic acid groups is prepared by Preparation Example 10.
[0064] Performance testing Detection Methods Test 1: The residual phosphorus concentration in the solution was tested by spectrophotometry, and the crystallization efficiency of phosphorus in the phosphorus purification solution was calculated according to the formula.
[0065] PPE=(P P -P S ) / P P ×100% Where: PEE is phosphorus crystallization efficiency (%); P P is the phosphorus concentration in the phosphorus purification solution (mg / L); P S is the phosphorus solubility in the supernatant after crystallization (mg / L).
[0066] Test 2: 1L of water from the Xi'an sewage treatment plant was placed in a beaker and numbered in sequence. Then, the synthetic flocculant of the present invention and the commercially available liquid PAC were added to the beaker and stirred at room temperature for 30 minutes. The dosage of the flocculant in the municipal sewage was 0.075mL / L. After the reaction was completed, the mixed solution was allowed to stand for 30 minutes, the supernatant was filtered to measure the residual phosphorus content, and the phosphorus removal efficiency of the sample was calculated according to the formula.
[0067] P E =(P0-P e ) / P0×100% Where P E is the phosphorus removal efficiency; P0 is the phosphorus concentration in the original water sample (mg / L); P e It is the residual phosphorus concentration (mg / L) of the water sample after flocculation treatment.
[0068] Table 1 Phosphorus crystallization rate Table 2 Phosphorus removal efficiency Phosphorus removal rate / % Example 1 65.92 Embodiment 17 64.68 Embodiment 18 64.16 Embodiment 19 64.83 Embodiment 20 64.45 Embodiment 21 67.48 Commercially available PAC 60.20 It can be seen from Example 1 and Comparative Example 1 and Table 1 that the molar ratio of Mg:N:P in the present application can make the phosphorus crystallization rate higher and the synthesized struvite can achieve a higher purity.
[0069] It can be seen from Example 9 and Comparative Examples 2-3 and Table 1 that conventional styrene-divinylbenzene resin itself has limited adsorption capacity for phosphorus and lacks specific adsorption sites. The styrene-divinylbenzene resin containing phosphonic acid groups has a strong affinity and specific binding ability for phosphorus, and can more selectively adsorb phosphorus from the phosphorus purification liquid, achieve efficient enrichment of phosphorus, and improve the removal rate of phosphorus. Acid-base treatment can adjust and optimize the surface properties of the resin. If acid-base treatment is not performed, subsequent treatment cannot achieve the desired effect.
[0070] It can be seen from Examples 1-7 and Table 1 that when the liquid-solid ratio is low, the amount of hydrochloric acid solution is relatively small, and the phosphorus compounds in the sludge residue cannot be fully contacted and dissolved. This will lead to incomplete leaching of phosphorus, so that the amount of phosphorus finally recovered is reduced. As the liquid-solid ratio increases, the hydrochloric acid solution can better penetrate into the sludge residue, fully react with the phosphorus compound, thereby improving the leaching efficiency of phosphorus. In the range of a given pH of 9-11, this alkaline environment is conducive to the crystallization of struvite. Suitable pH values can ensure that elements such as phosphorus, magnesium, and nitrogen undergo crystallization reactions according to the correct stoichiometric ratio to form high-purity struvite. The Mg:N:P ratio of (0.8-1.2):(1-1.6):1 in this application can effectively improve the phosphorus crystallization rate and improve the purity and quality of struvite.
[0071] In combination with Example 1 and Example 17-21 and in combination with Table 1, it can be seen that the ratio of chloromethyl ether to styrene-divinylbenzene resin in the present application can ensure that the resin successfully introduces enough chloromethyl functional groups, which is the basis of the subsequent phosphonation reaction, and can optimize the structure and performance of the resin, and avoid the destruction of the pore structure and the decrease in physicochemical stability caused by excessive cross-linking. Good pore structure is conducive to the exchange adsorption of ions and improves the removal efficiency of metal cations. By controlling the mass ratio of the reaction product and phosphorous acid, the content of the phosphonic acid group on the resin can be accurately adjusted. An appropriate amount of phosphonic acid groups give the resin a high affinity and selectivity for metal cations. The resin after acid-base treatment is immersed in a 0.5-1mol / L sulfuric acid solution, and the resin after transformation can better adapt to acidic environments, enhance the interaction with metal cations, and form more stable complexes or ion pairs. Transformation can further improve the adsorption capacity and selectivity of the resin to metal cations, remove the metal cations that affect phosphorus recovery, and increase the adsorption capacity of the resin, which is conducive to obtaining a high-purity phosphorus purification solution.
[0072] It can be seen from Example 1 and Example 8-16 and Table 1 that the liquid-solid ratio is controlled at 4-7mL / g, and this range can ensure that the hydrochloric acid solution is fully in contact with the sludge residue. Sufficient hydrochloric acid solution can keep the reaction system in good fluidity and promote the mixing and mass transfer process between the reactants. Under the condition of heating reflux stirring, the dissolution rate of the metal components in the sludge residue can be accelerated, and the reaction is effectively completed within 2-5h. The mass ratio of the primary solution of aluminum ferric chloride and sodium aluminate is in the range of (0.8-2.4): 1, so that the components in the primary solution of sodium aluminate and aluminum ferric chloride are fully reacted to form a polyaluminum ferric chloride with a higher degree of polymerization, so that the flocculant has an optimal charge density and molecular chain length, thereby enhancing its adsorption electrical neutralization, adsorption bridging and other flocculation mechanisms. Nano calcium carbonate, due to its small particle size and large specific surface area, can enhance the adsorption bridging effect in the aluminum ferric chloride flocculation system, improve electrical neutralization ability, improve flocculant stability, and improve flocculation effect and dephosphorization effect.
[0073] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for recovering phosphorus from sludge pyrolysis residue, characterized in that: The following steps are involved: Dry 90-110 parts by weight of the sludge pyrolysis residue at 105-110° C. for 1.5-2.5 hours, grind and sieve after drying; The sieved sludge pyrolysis residue is placed in a 0.1-0.8 mol / L hydrochloric acid solution at a liquid-solid ratio of 10-50 mL / g, reacted for 2-6 hours, and after the reaction, solid-liquid separation is performed to obtain a phosphorus-containing extract and residual sludge residue; The phosphorus-containing extract is treated with an adsorption resin for 2-3 hours to obtain a phosphorus-purified solution; The pH value of the phosphorus purification solution is adjusted to 9-11, and the magnesium, nitrogen and phosphorus are crystallized at a molar ratio of (0.8-1.2):(1-1.6):1 to obtain struvite.
2. The method for recovering phosphorus from sludge pyrolysis residue according to claim 1, characterized in that: The adsorption resin includes one of polyacrylamide resin, weakly acidic cation exchange resin, and styrene-divinylbenzene resin containing phosphonic acid groups.
3. The method for recovering phosphorus from sludge pyrolysis residue according to claim 1, characterized in that: The preparation method of the styrene-divinylbenzene resin containing phosphonic acid groups is as follows: The styrene-divinylbenzene resin is washed with deionized water until the conductivity of the deionized water is less than 50 μS / cm, and then dried; Styrene-divinylbenzene resin and anhydrous zinc chloride are mixed in a mass ratio of 10:(0.2-0.3), and toluene is added for stirring, chloromethyl ether is added to toluene, and the reaction temperature is controlled at 0-5°C. After the addition of chloromethyl ether, the temperature is raised to 30-35°C, and the reaction is carried out for 4-6 hours. After the reaction is completed, the reaction product is washed until the pH value is neutral and dried; The above reaction product and phosphorous acid are added to a solvent in a mass ratio of (1-1.5):1, mixed, heated to 100-120°C, and reacted for 6-8h; After the reaction is completed, the reaction product is washed to neutrality and then dried to obtain a styrene-divinylbenzene resin containing a phosphonic acid group.
4. The method for recovering phosphorus from sludge pyrolysis residue according to claim 3, characterized in that: The phosphonic acid group-containing styrene-divinylbenzene resin is further treated as follows: The styrene-divinylbenzene resin containing phosphonic acid groups is soaked in a hydrochloric acid solution with a mass concentration of 2-5%, and then the resin is washed to neutrality after soaking for 4-6 hours. The resin is then soaked in a sodium hydroxide solution with a mass concentration of 2-5%, and then washed to neutrality after soaking for 4-6 hours. Soak the acid-base treated resin in 0.5-1 mol / L sulfuric acid solution for 2-4 hours.
5. A flocculant, characterized in that: The flocculant is prepared from the excess sludge residue as claimed in claim 1.
6. A method for synthesizing a flocculant according to claim 5, characterized in that: The following steps are involved: Mix a hydrochloric acid solution with a mass concentration of 10%-30% with the remaining sludge residue at a liquid-solid ratio of 4-7 mL / g, heat to 80-140°C, reflux and stir for 2-5 hours, and after the reaction is completed, a primary aluminum ferric chloride solution can be obtained; The aluminum ferric chloride primary liquid is mixed with sodium aluminate in a mass ratio of (0.8-2.4):1, and a polymerization reaction is carried out at 60-100°C to obtain a polyaluminum ferric chloride solution flocculant after the reaction is completed.
7. The method for synthesizing a flocculant according to claim 6, characterized in that: When the aluminum ferric chloride primary liquid is mixed with sodium silicate, nano calcium carbonate is added, the particle size of the nano calcium carbonate is 30-80nm, and the addition amount of the nano calcium carbonate is 1.5-3.5% of the mass of the primary liquid.
8. Use of the flocculant according to any one of claim 5, characterized in that: The flocculant is applied to municipal sewage.
9. The use of the flocculant according to claim 8, characterized in that: The dosage of the flocculant in municipal sewage is 0.025-0.1 mL / L.
Citation Information
Patent Citations
Heavy-metal-containing electroplating wastewater treatment and heavy metal recycling method
CN102531233A
Resource utilization method of sludge pyrolysis biochar
CN110255845A
Iron ion adsorption resin, preparation method and application thereof in removal of iron ions in solution
CN111686700A
Preparation method of high-efficiency high-selectivity polyol adsorption material
CN112724455A
Polyaluminum ferric chloride prepared from municipal sludge drying pyrolysis residues and composite flocculant
CN114804315A
Cited By
Method for recovering nitrogen and phosphorus elements from municipal sludge
CN119858904A
Preparation of sludge-based flocculation-nutrition multifunctional agent and application of sludge-based flocculation-nutrition multifunctional agent in recycling of muck slurry
CN120460447A
Method for preparing deep phosphorus extraction synergistic residue-based adsorbent applied to sewage sludge
CN120919967A